Domestic work stress and self-rated psychological health among women: a cross-sectional study in Japan - Eri Maeda; Kyoko Nomura; Osamu Hiraike; Hiroki Sugimori; Asako Kinoshita; Yutaka Osuga (Komiyama Printing Co. Ltd, 2019)
Abstract Background Despite the huge burden of domestic work on women in Japan, its effects on their health have been poorly investigated. We aimed to assess the association between domestic work stress and self-rated psychological health among women. Methods We conducted a cross-sectional survey using an online social research panel in February 2018. Participants were 2,000 women with paid work (the "workers" group) and 1,000 women without paid work (the "homemakers" group), aged between 25 and 59 years old and living with a partner. Self-rated psychological health (Mental Health and Vitality scales of the Japanese SF-36), occupational and domestic work stress (the Brief Job Stress Questionnaire), the 10-item Work-Family Conflict Scale, and sociodemographic factors were assessed. Results The workers had lower domestic job control and higher support from a partner and their parents than the homemakers (p < 0.001), whereas domestic job demand and psychological health were similar between the groups. After adjustment for the covariates using multiple linear regression models, better psychological health was significantly associated with lower domestic job demand, higher domestic job control, and having a young child in both groups. In addition, work-family conflicts and occupational job stress among the workers and caregiving among the homemakers showed negative associations with psychological health. Conclusion Self-rated psychological health in women was associated with domestic work stress regardless of employment status. To promote women's health, we need to take into account the effects of domestic work, work-family conflicts, and social support from families, as well as occupational factors.